Absorptive Capacity, Business Venturing and Performance: Corporate Governance Mediating Roles - Cosmas Ikechukwu Asogwa (Taylor & Francis Group, 2020)
This study offers insight through Structural Equation Modeling (SEM) into the joint impact of corporate absorptive capacity and corporate new business venturing on the performance of manufacturing firms in Nigeria as moderated by the quality governance mechanisms. Using the structured survey design, and respondents’ data from 330 employees of manufacturing firms, we provide evidence that both absorptive capacity and corporate new venturing entrepreneurship dimensions do not directly yield significant positive impact on firms’ performance. Rather, the significant effect depends on the quality of the corporate governance mechanisms. Firms’ absorptive capacity as measured by acquisition, assimilation (potential absorptive capacity), transformation, and knowledge exploitation (realized absorptive capacity) only resulted in value creation when mediated by key governance mechanisms including frequency of board meeting, and the presence of independent directors. Similar effect was detected on the effect of corporate new business entrepreneurship dimensions including innovation, proactivity, new business venturing and strategic renewal on firms’ performance in manufacturing sector. The path analysis showed that optimal board size, frequency of board meeting and the presence of independent directors jointly shape the way corporate new business entrepreneurship dimensions affect firms’ performance. By implication, weak governance occasioned agency problems that reduce the potential of corporate entrepreneurship to influence corporate financial performance positively. Overall, firms that wish to reap the benefit of knowledge management and new business venturing should develop their governance structures. Thus, board size and independent directors are expected to be optimal to enhance and achieve sufficient monitoring while frequency of board meeting should be given a priority to encourage knowledge sharing that will translate into higher financial performance.